0223 A Single Episode Of Binge Alcohol Drinking Disrupts Sleep Homeostasis To Cause Sleep Disruptions. (27th April 2018) - Sharma, R; Sahota, P; Thakkar, M M
Abstract: Introduction: Binge alcohol drinking, a risky pattern of alcohol consumption, is highly prevalent in United States. Due to its high prevalence and significant association with severe long-term health and social consequences, binge drinking is considered a major public health issue. Binge alcohol drinking causes severe sleep disruptions. Sleep disruptions in alcoholics are associated with increased risk for substance abuse. How does binge alcohol consumption affect sleep regulation to cause sleep disruptions? Methods: Adult male C57BL/6J mice were used as animal model. Four experiments were designed. The first experiment verified binge pattern of alcohol self-administration. Second experiment monitored the effects of binge alcohol consumption on spontaneous sleep-wakefulness. The third experiment evaluated the effects of binge alcohol consumption on electrophysiological and biochemical indicators of sleep homeostasis using sleep deprivation-recovery sleep paradigm. The fourth experiment examined expression of genes controlling sleep homeostasis. Results: Our results are as follows: 1) when allowed to self-administer alcohol in a non-stressful environment, mice consumed alcohol in a binge pattern. 2) While sleep-wakefulness remained unchanged during binge drinking session, significant increase in NREM sleep was observed during 4 hours of dark period post-binge. Although the timing of sleep onset (at lights-on) remained unaffected, increased wakefulness, reduction in NREM and REM sleep was observed during subsequent sleep (light) period. 3) Mice exposed to binge drinking did not develop sleep pressure during sleep deprivation. Cortical theta power and basal forebrain adenosine levels did not increase during sleep deprivation; NREM sleep and NREM delta power did not increase during recovery sleep. 5) While binge alcohol drinking did not affect the expression of adenosine kinase and A1 receptor, expression of equilibrative nucleoside transporter 1 (ENT1) was significantly reduced. Conclusion: These results suggest that binge alcohol consumption induced downregulation of ENT1 expression may disrupt sleep homeostasis and cause sleep disturbances. Support (If Any): None